“What Deeply Irritates You”: Subjective Evaluation and Societal Evidence of (Socio) Linguistic Phenomena - Sene, Marcus Garcia [UNESP]; Biazolli, Caroline Carnielli; Brandão, Silvia Maria [UNESP] (Springer Nature, 2023)
Language is a social practice subject to the evaluation of the speaker on the one hand and the evaluation of the listener on the other. Therefore, along with the knowledge of how people effectively use the language, it is necessary to include the way they perceive, evaluate, and react to diversified linguistic uses. In general, such evaluation materializes in societal evidence (Garrett P, Coupland N, Williams A, Int J Appl Linguistics, 15, 411, https://doi.org/10.1111/j.1473-4192.2005.00100d.x, 2003) that may be negative or positive regarding a variety, variant, or specific linguistic item. Thus, the objective of this chapter is to analyze societal evidence that expresses subjective evaluations of speakers concerning linguistic uses considered “irritating.” The data analyzed herein, which integrate the larger project “Linguistic prejudice online and offline: phenomena categorization, social profiles and subjective evaluation” (Sene MG, Brandão SM, Biazolli CC, Preconceito linguístico na rede e fora dela: categorização, perfis sociais e avaliação subjetiva. Open Science Framework. https://osf.io/6ymrv/. Accessed 09 June 2022, 2019; Brandão SM, Biazolli CC, Sene MG, Falange Miúda, 5(2), 222–243, 2020), was collected using the social networking platform Facebook, from the post “Mention a Portuguese mistake that deeply irritates you,” published in the group LDRV – Taubaté New Global Era. Among the phenomena presented as “irritating,” it is possible to find the uses of mim + verb in the infinitive (para mim fazer), agente instead of a gente and mais rather than mas.
Keywords: Linguistic prejudice; Linguistic variation; Societal evidence; Subjective evaluation